Dampak Serikat Buruh Terhadap Tingkat Upah Buruh Sektor Swasta di Indonesia - Sulistyaningrum, Eny; Kurniawan, Septyono (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252)DO - 10.24843/JEKT.2017.v10.i02.p09, 2017)
Labors have weaker bargaining position than the employer because of higher proportion of labor supply than demand. Employment in Indonesia only reaches 60 percent of the labor force. Labor union is formed to provide a more bargaining position for labor in relation to the employer. This study aims to analyze the impact of labor union toward labor wage, especially for workers who works in the private sector in Indonesia. The data used is the data from IFLS wave 4 and 5. This paper using PSM with kernel matching method to analyze the data. The results show that on average, private sector workers in Indonesia who participate in union membership will have a higher wage of 17 percent compared with workers outside the union.